2020
DOI: 10.1097/eja.0000000000001375
|View full text |Cite
|
Sign up to set email alerts
|

Adverse respiratory events with sevoflurane compared with desflurane in ambulatory surgery

Abstract: BACKGROUND An increasing number of studies have concluded that the number of adverse events in the upper airway caused by desflurane does not differ significantly from the number of adverse events caused by sevoflurane. The advantages of desflurane in ambulatory surgery should be reassessed. OBJECTIVES The aim of this study was to compare adverse respiratory events and recovery outcomes in patients undergoing desflurane or sevoflurane-based anaesthesia in ambulatory sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…In one large cohort study, desflurane was associated with an increased rate of perioperative respiratory adverse events (RR 2.17 (95% CI 1.5–3.15) p < .0001) when compared to other inhalational agents 50 . Further, in a systematic review and meta‐analysis of 13 trials (3 pediatric) comparing sevoflurane to desflurane, the authors found that desflurane was associated with an increased rate (RR 1.59 (95% CI 1.15 to 2.20)) of respiratory complications such as laryngospasm and bronchospasm 51 . This difference, however, did not persist when analyzing subgroups such as children or patients in whom an endotracheal tube was used.…”
Section: Main Articlementioning
confidence: 97%
See 1 more Smart Citation
“…In one large cohort study, desflurane was associated with an increased rate of perioperative respiratory adverse events (RR 2.17 (95% CI 1.5–3.15) p < .0001) when compared to other inhalational agents 50 . Further, in a systematic review and meta‐analysis of 13 trials (3 pediatric) comparing sevoflurane to desflurane, the authors found that desflurane was associated with an increased rate (RR 1.59 (95% CI 1.15 to 2.20)) of respiratory complications such as laryngospasm and bronchospasm 51 . This difference, however, did not persist when analyzing subgroups such as children or patients in whom an endotracheal tube was used.…”
Section: Main Articlementioning
confidence: 97%
“…50 Further, in a systematic review and meta-analysis of 13 trials (3 pediatric) comparing sevoflurane to desflurane, the authors found that desflurane was associated with an increased rate (RR 1.59 (95% CI 1.15 to 2.20)) of respiratory complications such as laryngospasm and bronchospasm. 51 This difference, however, did not persist when analyzing subgroups such as children or patients in whom an endotracheal tube was used. Specifically, desflurane can lead to increased airway resistance and thus, in those with a history of URTI, or any other pulmonary disease associated with airway susceptibility, it should be avoided.…”
Section: Maintenancementioning
confidence: 99%
“…In addition, the possibility of drug-interaction with desflurane cannot be excluded. Especially, desflurane may induce increased HR and airway irritation [ 38 ] which may result in significant effects in our study. There was also another limitation in the research design.…”
Section: Discussionmentioning
confidence: 90%
“…Among all the volatile anesthetics currently used, desflurane has the lowest blood solubility, suggesting the fastest induction and awakening [4]. Despite the advantage of faster recovery, even compared to sevoflurane, undesirable effects, including airway stimulation, tachycardia, and greenhouse effect, can limit the use of desflurane [16][17][18][19]. In such cases, sevoflurane can be mostly chosen for anesthesia induction and maintenance due to its little airway stimulation effect.…”
Section: Discussionmentioning
confidence: 99%